Factores de riesgo que influyen en la retención urinaria en los pacientes posoperados inmediatos de la Clínica Good Hope, Lima - Idrogo Sánchez, Dámaris (2019)
Objective: Identify the risk factors influencing urinary retention in patients post operated immediate clinical goodHope, April 2012. Material and Methods: The study was quantitative, descriptive, transversal, not experimental,type of design cases and controls. comprised of 85 patients immediate posoperados. A guide to data collection withthe purpose of knowing the risk factors associated in urinary retention was applied. The analysis was performedthrough Odds Ratio (OR) of cross products with its respective confidence interval (CI) and significance at 95%.Results: 51.8% Of the sample belonging to the female sex; more than half (58.8%) have more than 40 years.The postoperados values are interpreted as possibilities of presenting urinary retention were: the posoperados witha history of 11.6 times prostate adenoma risk reasons; seized by Traumatology presented 4.4 times risk reasonsand the subject under spinal anesthesia had 11 times risk reasons. Conclusions: 9 Risk factors were identified, ofwhich 3 of them obtained more reason of advantage of presenting urinary retention in the immediate postoperativeconcluding that patients operated on under spinal anesthesia are more likely to develop urinary retention in theimmediate postoperative.